The Role of Citizen Forums in Monitoring Public Services - Kalalo, Rieneke Ryke; Yudhianto, Kresna Agung; Idris, Dany Luqyana; Sitompul, Gabriel Amadeus; Lamsir, Seno (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Public service is a system, meaning that citizen forums or the public as applicants or users of services must be given the broadest possible access to the problem-solving and decision-making processes in the provision of public services. The principle of openness plays a crucial role in establishing quality public services. This study uses a qualitative approach with descriptive methods. This approach was chosen because it aims to deeply understand how citizen forums play a role in overseeing public services, as well as the dynamics of interactions between citizens and the government within these forums. The research results have found that citizen forums have a strategic role in overseeing public services, namely as a forum for public participation, a mechanism of social control, a medium for dialogue and collaboration, and a driver of transparency and accountability. However, the success of citizen forums is highly dependent on the capacity of citizens, support for government policies, and the political will of officials to be open to public criticism and input.